COVID-19's impact on lung tissue: A case report. (March 2022) - Crudeli, Connor; Zilberman, Brian; Williams, Jennifer; Burg, Jennifer; Shersher, David
Abstract: Introduction: The novel coronavirus has spread globally, however, there continues to be little information regarding management, treatment, and complications encountered by infected patients. Prior to COVID-19, guidelines had been well established for managing empyema, however, evidence is lacking for such patients possessing a COVID-19 infection. In the spirit of collaborative knowledge, we endeavor to present a COVID-19 case from our tertiary care institution. Case presentation: A 59-year-old Caucasian male with a past medical history of chronic obstructive pulmonary disease and hypertension was transferred to our hospital for escalation of care of COVID pneumonia. Pharmaceutical treatment included an IL-6 inhibitor (tocilizumab). The patient's hospital course was complicated by superimposed bacterial pneumonia with development of a loculated pleural empyema. On day 57, a left anterolateral muscle-sparing thoracotomy and complete pulmonary decortication was performed. The patient made a successful recovery. Clinical discussion: This patient's vascular dysfunction associated with shunting secondary to pulmonary microthrombi, provides rationale for the liberal use of therapeutic anticoagulation in COVID patients. The superimposed bacterial pneumonia raises concerns over the use of tocilizumab in COVID-19 patients. It is necessary to understand whether current guidelines will need to be amended for the treatment of coagulopathies to avoid pulmonary vascular dysfunction. Conclusion: Thoracic surgery can be carried out safely, both for patients and practitioners, during the pandemic. Microvascular occlusions within the pulmonary vasculature contribute to the severe hypoxia and need for anticoagulation in severe COVID-19 cases. Clinical pathways for common clinical presentations, such as empyema, may need to be re-evaluated during this global crisis. Highlights: Varying pathology observed in COVID-19 patients undergoing pulmonary resection Vascular dysfunction associated with shunting secondary to pulmonary microthrombi Microvascular occlusions contribute to severe hypoxia and need for anticoagulation. Thoracic surgery can be carried out safely during the pandemic. Clinical pathways for COVID-19 patients may need to be re-evaluated.